Monetary Instruments Against the Indonesian Sharia Stock Index: Moderation in Gross Domestic Product - Fitrianingsih, Dwi; Fafurida (Universitas Negeri Semarang, 2025)
The Indonesian Sharia Stock Index (ISSI) is an indicator that represents the price performance of all sharia-compliant stocks listed on the Indonesia Stock Exchange (IDX). Over the past three years, ISSI capitalization has experienced significant growth. However, this development is still influenced by the dynamics of external factors, particularly macroeconomic variables such as inflation, the IDR exchange rate, and the BI 7-Day Reverse Repo Rate (BI 7-Day RR). The purpose of this study is to analyze the effect of inflation, the IDR exchange rate, and the BI 7-Day RR on the ISSI and to examine the role of GDP in moderating this relationship. The study uses a quantitative associative approach with Indonesian time series data for the 2021–2023 period. Analysis techniques include classical assumption testing, multiple linear regression with a Moderated Regression Analysis (MRA) approach, and hypothesis testing. The results indicate that inflation has no significant effect on the ISSI. Conversely, the IDR exchange rate and the BI 7-Day RR were shown to have a significant effect on the ISSI. Other findings indicate that GDP strengthens the influence of the IDR exchange rate and the BI 7-Day RR on the ISSI, but does not moderate the relationship between inflation and the ISSI.